SONAR 5 Overdrive!: Expert Quick Tips - Christensen, James (Course Technology PTR, 2006)
If you are an experienced SONAR user and want to take your skills to the next level, this is the book for you. Packed with advanced tips, tricks, and useful screenshots, SONAR 5 Overdrive! will help you find faster results, avoid common pitfalls, and save yourself headaches while you unleash the program's full power. There is something for everyone from setting up to sharing your files with others, and from recording and editing to creating the final mastered tracks. Use the book as a reference to turn to when trying to solve a problem or as a source for new ideas. Each advanced tip is concise and to the point, with numbered steps where appropriate, so you can spend less time in the book and more time creating awesome music and sound!